POTENSI ASAM LEMAK DARI MIKROALGA Nannochloropsis sp SEBAGAI ANTIOKSIDAN DAN ANTIBAKTERI - Agustini, Ni Wayan Sri (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- In Indonesia, the use of microalgae is still lacking, therefore, the antibacterial and antioxidant activity of the extract fatty acids from microalgae Nannochloropsis sp. Nannochloropsis sp biomass. extracted by soxhletasi with petroleum ether and ethanol, whereas the fatty acid extraction method by Indonesian National Standard. Antibacterial activity by disc diffusion method and antioxidant activity using the method of reduction of free radicals (DPPH). The results showed that the petroleum ether extract showed antibacterial and antioxidant activity better than the ethanol extract. The results of the identification of fatty acids in petroleum ether extract was dodecanoic acid (18.88%), while the ethanol extract was hexadecanoic acid (14.02%).Â Keywords: antioxidant, antibacterial, fatty acid, Nannochloropsis sp